Eligibility of the Conservation Education Guidebook for Senior High School - Jesisca Jesisca; Ruqiah Ganda Putri Panjaitan*; Afandi Afandi (Universitas Syiah Kuala, 2023)
Indonesia does not yet have a curriculum that implements conservation education, several schools have carried out conservation activities but do not yet have guidebooks or written documents related with the programs, so it is necessary to prepare a conservation education guidebook. This study aims to determine the eligibility of a high school conservation education guidebook. This study uses the RD research method with the ADDIE limited to the development stage. The eligibility test of the conservation education guidebook was carried out by validating by five validators with the validation sheet assessment instrument and analyzed using Aiken's content validity and ICC (intraclass correlation coefficient) reliability. The aspects assessed in the validation test are material aspects, presentation, language, and guidebook graphics. The results of Aiken's validity were obtained for the material aspect, namely 0.92 very high categories, presentation aspect, namely 0.87 very high categories, language aspect, namely 0.93 very high categories, and graphic aspect, namely 0.92 very high categories. The average validity of the four aspects is 0.92 in the very high categories. The results of the ICC reliability analysis showed a reliability value of 0.965 and agreement between validators was at a very good criteria index. It can be concluded that the high school conservation education guidebook is eligible to use